TINJUAN HUKUM TERHADAP PENARIKAN KEMBALI HARTA YANG TELAH DIHIBAHKAN MENURUT KOMPILASI HUKUM ISLAM - Dina Paramitha Hefni Putri; Ahmad Maulana Bahri (The Juris, 2021)
The grant is a contract that is still often done by the people of Indonesia, this may be due to the grants including acts that are recommended or prescribed by religion. However, by most people, a grant is only understood as a form of giving, without realizing what is meant by the grant itself. Grants, namely KHI and Civil Code do not allow it. Imam Syafi'i said that if the grant has been considered perfect by receiving the permission of the grant giver, or the party giving the grant has handed over the goods given, then such a grant has taken place perfectly. A grant that goes on like that is not valid to be withdrawn, except for a father. Legislation that regulates the issue of withdrawal of grant items includes the Civil Code (KUH Perdata), Sharia Economic Law Compilation (KHES), and Islamic Law Compilation (KHI). In the three laws and regulations include all matters relating to the grant, especially regarding the withdrawal of the grant items.